2022
DOI: 10.1007/s40520-022-02121-z
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength predicts length of hospital stay in an abdominal surgical setting: the role of frailty beyond age

Abstract: Background Chronological age per se cannot be considered a prognostic risk factor for outcomes after elective surgery, whereas frailty could be. A simple and easy-to-get marker for frailty, such as handgrip strength (HGS), may support the surgeon in decision for an adequate healthcare plan. Aims The aims of this study were to: (1) determine the prevalence of frailty in an abdominal surgery setting independent of age; (2) evaluate the predictive validity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…Aging is an inevitable process for all humans, and the global aging population is increasing in parallel to improved quality of life and medical advances [1]. Elderly individuals constitute one of the most vulnerable populations and are at high risk for various nutritional issues and comorbidities including gastric cancer [2][3][4]. Indeed, the rate of elderly patients with gastric cancer is increasing and their high mortality rate is an issue [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Aging is an inevitable process for all humans, and the global aging population is increasing in parallel to improved quality of life and medical advances [1]. Elderly individuals constitute one of the most vulnerable populations and are at high risk for various nutritional issues and comorbidities including gastric cancer [2][3][4]. Indeed, the rate of elderly patients with gastric cancer is increasing and their high mortality rate is an issue [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, several studies have investigated the effect of hospital volume on gastric cancer surgery outcomes, leading to the concept that centralization results in better outcomes, acting as a proxy measure for various processes and providing the advantages of a qualified multidisciplinary team and a comprehensive multidimensional assessment [ 85 , 86 ], easier access to sophisticated cancer imaging equipment, availability of skilled surgeons, and better postoperative care facilities [ 30 , 87 , 88 , 89 , 90 ]. In this regard, an experienced radiologist with dedicated skills in gastric cancer metastasis detection (i.e., gastric carcinomatosis) is fundamental to allow for better patient selection [ 91 ].…”
Section: Predictors For Good Quality Of Carementioning
confidence: 99%
“…In 2021, the OVHIPEC group, using the EORTC questionnaires, concluded that the addition of HIPEC to interval CRS does not negatively impact health-related quality of life [ 144 ]. Opting for therapeutic choices considering the patients’ clinical conditions [ 150 ], comorbidities, age and frailty status is necessary to improve their quality of life and life expectancy [ 151 ].…”
Section: Treatment Of Ovarian Cancer Metastatic Peritoneal Surface Ma...mentioning
confidence: 99%